EDUCATION AND FUTURE WORK ATTITUDES OF STUDENTS IN POLAND AND LITHUANIA: A COMPARATIVE ANALYSIS - Kumpikaite - Valiūniene, Vilmante; Rollnik-Sadowska, Ewa; Glińska, Ewa (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Increasing the employment among young people is one of the main objectives of the European Union labour market policy. On the one hand, labour market indicators of youths are worse than the ones for the population as a whole. Moreover, the EU countries face NEETs phenomena when young people are not in education, employment and training. Simultaneously, the strong aging process in Europe and demographic changes determine the need for a particular focus on young people who are an important part of future labour force. It is crucial to equip young people with the skills and competencies tailored to the needs of employers, which also would be consistent with the attitudes and expectations of young people. That is why the authors of the paper decided to take into consideration the work and education attitudes of students in two European countries - Poland and Lithuania. These neighbouring EU member states went through comparable historical and political conditions, which influenced their economic situations also in the area of labour market. However, those countries followed different educational reforms. Lithuania implemented basic dual learning and Poland still represents more theoretical orientation in tertiary education. The research aim of the paper is to identify the differences in education and future work attitudes of Polish and Lithuanian students. Those differences were diagnosed taking into account: an assessment of own skills for a 'dream' job, perceptions of the impact of environmental factors on a future career, as well as a diagnosis of motivators to work.The chosen research methods were both secondary data analysis as well as realisation of the primary quantitative research among Polish and Lithuanian students. The survey was conducted among 500 students - roughly in half from each country. The comparison showed large similarities in the factors affecting the motivation of students to work as well as some differences in the perception of the impact of the environment on the future career. The biggest differences among students from two countries were identified in the evaluation of skills needed to find employment.